Evaluación genética de la eficiencia en la producción de leche de dos hatos en las parroquias de Guaytacama y San Buenaventura. - Caiza Jácome, Jéssica Estefanía (2020)
The study objective was to evaluate the productive efficiency of two dairy herds located in the province of Cotopaxi, Latacunga canton, Guaytacama and San Buenaventura parishes, related to the heritability obtained from their fathers, the breeding value (breeding value) of 121 adult cows with ages ranging between 5 to 9 years and 45 males is estimated. , belonging to the Hcda. Guaytacama 85 cows and 31 bulls, in the Hcda. Santa Rosa 36 cows and 14 bulls were analyzed. Data of the animals corresponding to: identification number of the animals, identification of the father, identification of the mother, sex of the animal, breed, age, lactation number, total production corresponding to lactation were tabulated, through the mathematical model BLUP90 to estimate the breeding values (CV), based on a mixed model considering milk production. A total of 45 males were evaluated, giving as results that in the Guaytacama Hcda 41.93% of bulls are efficient while in the Hcda. Santa Rosa 57.14% of bulls are efficient in milk production, thus having an average efficiency of 55.38% for all cows analyzed. Concluding that the selection of breeding animals is deficient, one of the factors that could predispose to the expression of the genes of an animal is the interaction genotype environment (IGA), thus, when selecting males or their semen, the producers are based on catalogs of animals that develop in different environments, which is why when having daughters of certain males they have a loss since there is interaction genotype